HAMBATAN BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SDN KAMAL 1 - Nurhalisa; Putri Aura Condrowati; Sarifatur Rofi’ah; Rika Wulandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify the obstacles faced by fourth-grade students of SDN Kamal 1 in learning Pancasila Education. The research method used a qualitative approach with a case study design. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that the most dominant obstacles were lack of interest in learning, difficulty understanding abstract concepts, limited learning media, the influence of the social and family environment, limited time, differences in student abilities, and a lack of interesting and participatory learning activities.